Determinación de oftalmopatias en bovinos faenados en el camal municipal del cantón Machala - Chapin Viñan, Henry Antonio (2007)
The present investigation you carries out during the mese he/she gives June, Julio and August gives the 2007, in the Municipal carnal he/she gives the Canton Machala and he/she had as objectives: 1. to determine the presence gives ocular alterations in the bovine faenados in the municipal carnal he/she gives the canton Machala. 2. to establish the relationship gives the positive cases according to their origin, race, sex and age. " The number gives animal sampled it was he/she gives 260 bovine, give which 44 were as positive and 216 negatives, giving this a percentage gives positive cases he/she gives 16,92%. The Canton with the biggest number gives positive cases to some type he/she gives oftalmopatias it was Zaruma with 3,08%.